Repoliticizing the Ancient Greek City, Thirty Years Later *. Issue 3 (September 2014) - Azoulay, Vincent; Krieger, Angela
Abstracts: Thirty years after Nicole Loraux published her 1986 article in L'Homme, this study revisits the question of political experience in the ancient Greek world. Its aim is to demonstrate the importance of the two definitions of the term "politics" as conceived by the Ancient Greeks. On the one hand, the political was conceived as an ensemble of activities with no specific institutional substance or form, a sphere of action that has no direct equivalent in the modern state, but rather relates to very varied experiences and practices undertaken in the context of conflict. On the other hand, politics was understood not only as organized access to different institutions, but also as the way in which a community structured and defined itself. Taking the Athenian crisis of 404-403 BCE as a case study, in particular the speech of Cleocritus preserved in Xenophon's Hellenica, this paper proposes a new way of thinking about this dual expression of collective life. Far from the reconciliatory reading of Cleocritus' speech proposed by Loraux, his appeal for harmony bears witness, in the turmoil and tension of events, to the way that politics (in the institutional sense) was sidelined to the exclusive benefit of the political and the collective practices associated with it. In conclusion, this case study opens up a more general consideration of the meaning of the "event" and its epistemological significance. By considering the crisis of 404-403 BCE at the heart of the "regimes of historicity" that characterized the history of Athens between the fifth and fourth centuries BCE, this article aims to provide a clearer articulation of the foundational moments and established functioning of Greek democracy.